1999
DOI: 10.4315/0362-028x-62.10.1115
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Survival of Verocytotoxin-Producing Escherichia coli O157 in Meats Obtained from Retail Outlets in The Netherlands

Abstract: In 1996 and 1997, 2,941 fresh and processed meat products obtained from supermarkets and butcher shops in The Netherlands were examined for the presence of verocytotoxin-producing Escherichia coli of serogroup O157 (O157 VTEC). Additionally, the fate of O157 VTEC in raw meat products stored at low temperatures and the effect of different additives were evaluated. O157 VTEC strains were isolated from 6 (1.1%) of 571 samples of raw minced beef, 2 (0.5%) of 402 samples of raw minced mixed beef and pork, 1 (1.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 0 publications
4
23
2
3
Order By: Relevance
“…The lack of STEC in poultry meat from the NARMS program was consistent with reports from Schroeder et al, who failed to detect STEC in retail chicken (51 ground chicken samples and 212 whole chickens) and turkey (50 ground turkey samples and 194 turkey breasts) samples from the Washington, DC, area (46). Similarly, Brooks et al failed to isolate STEC from 36 chicken samples in New Zealand (6,46), and Heuvelink et al did not find STEC O157 in raw chicken (n ϭ 744) and poultry products (n ϭ 75) in The Netherlands (26). However, Samadpour et al recovered 4 STEC isolates from 33 chicken breasts and 1 STEC isolate from 15 turkey samples (12), and Doyle and Schoeni found STEC O157 in 4 of 263 poultry products (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of STEC in poultry meat from the NARMS program was consistent with reports from Schroeder et al, who failed to detect STEC in retail chicken (51 ground chicken samples and 212 whole chickens) and turkey (50 ground turkey samples and 194 turkey breasts) samples from the Washington, DC, area (46). Similarly, Brooks et al failed to isolate STEC from 36 chicken samples in New Zealand (6,46), and Heuvelink et al did not find STEC O157 in raw chicken (n ϭ 744) and poultry products (n ϭ 75) in The Netherlands (26). However, Samadpour et al recovered 4 STEC isolates from 33 chicken breasts and 1 STEC isolate from 15 turkey samples (12), and Doyle and Schoeni found STEC O157 in 4 of 263 poultry products (15).…”
Section: Discussionmentioning
confidence: 99%
“…Such variations could lead to a big difference in results, since isolation of STEC from stx-positive samples was found to be relatively difficult due to the small number of bacterial cells or the occurrence of free stx-carrying phages in meat samples (43,45). In terms of isolation method, instead of picking multiple colonies randomly from one plate and testing each of them (17,26), colony hybridization with a stx probe would more conveniently detect any STEC in all colonies on each plate and yield more accurate results (18,45). The level of STEC contamination (Ͻ1%) in the NARMS ground beef appeared low compared to reports from other investigators, but caution should be exercised in interpreting this low prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Data from several European countries showed that the VTEC prevalence in minced beef ranged from 0 % to 3 % (EFSA and ECDC, 2013). The reported prevalence of VTEC in minced beef in various European studies is 0.76 % in the UK (Chapman et al, 2000;, 2.8 % in Ireland (Cagney et al, 2004), 0.12 % in France , 0.18 % in Belgium (Tutenel et al, 2003), 0.43 % to 13 % in Italy (Conedera et al, 2004;Parisi et al, 2010), 11.5 % in Spain (Mora et al, 2007), 1.1 % in the Netherlands (Heuvelink et al, 1999) and 2.3 % in Switzerland (Fantelli and Stephan, 2001). Pathogenic E. coli, such as VTEC, have a reported minimum growth temperature of 6 ºC to 7 ºC, an optimum temperature of 35 °C to 42 °C (James and James, 2014) and will grow between pH 4.4 and 10.0 and a minimum a w of 0.95 (Desmarchelier and Fegan, 2003).…”
Section: Verocytotoxigenic Escherichia Coli (Vtec)mentioning
confidence: 99%
“…Heuvelink, Zwartkruis-Nahuis, Beumen, and de Boer (1999) reported that 6 out of 571 samples analysed in the Netherlands (1.1%) were positive for E. coli O157:H7. In France, a study by Vernozy-Rozand et al (2002) reported a low 0.12% (4/3450) E. coli O157:H7 prevalence in minced beef.…”
Section: Introductionmentioning
confidence: 98%